Growth behavior and resource potential evaluation of gas hydrate in core fractures in Qilian Mountain permafrost area, Qinghai-Tibet Plateau - Qing-guo Meng; Chang-ling Liu; Zhen-quan Lu; Xi-luo Hao; Cheng-feng Li; Qing-tao Bu; Yun-kai Ji; Jia-xian Wang (China Geology)
ABSTRACT: The Qilian Mountain permafrost area located in the northern of Qinghai-Tibet Plateau is a favorable place for natural gas hydrate formation and enrichment, due to its well-developed fractures and abundant gas sources. Understanding the formation and distribution of multi-component gas hydrates in fractures is crucial in accurately evaluating the hydrate reservoir resources in this area. The hydrate formation experiments were carried out using the core samples drilled from hydrate-bearing sediments in Qilian Mountain permafrost area and the multi-component gas with similar composition to natural gas hydrates in Qilian Mountain permafrost area. The formation and distribution characteristics of multi-component gas hydrates in core samples were observed in situ by X-ray Computed Tomography (X-CT) under high pressure and low temperature conditions. Results show that hydrates are mainly formed and distributed in the fractures with good connectivity. The ratios of volume of hydrates formed in fractures to the volume of fractures are about 96.8% and 60.67% in two different core samples. This indicates that the fracture surface may act as a favorable reaction site for hydrate formation in core samples. Based on the field geological data and the experimental results, it is preliminarily estimated that the inventory of methane stored in the fractured gas hydrate in Qilian Mountain permafrost area is about 8.67×1013 m3, with a resource abundance of 8.67×108 m3/km2. This study demonstrates the great resource potential of fractured gas hydrate and also provides a new way to further understand the prospect of natural gas hydrate and other oil and gas resources in Qilian Mountain permafrost area.©2023 China Geology Editorial Office.